RELIGIOUS CONSIOUSNESS IN UKRAINE IN THE TRANSIATION OF THE TRADITIONAL SOCIO-CULTURAL EXPERIENCE - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article discusses the historical continuity of the ideological foundations of the traditional religious and secular ideologies in Ukraine and their impact on the religious consciousness